The Influence of Marketing Strategy and Product Quality on the Competitiveness of Coffee Products at Kiro Lahat Coffee Shop - Vilda Tiara Ayu Dewanti; Markus Markus; Emila Sholiha (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how marketing strategy and product quality partially and simultaneously influence the competitiveness of coffee products at Kiro Lahat Coffee Shop. The sample size for this study was 42 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, to produce a regression equation . The results showed a significant effect between marketing strategy and the competitiveness of coffee products at Kiro Lahat Coffee Shop, and a significant effect between product quality and the competitiveness of coffee products at Kiro Lahat Coffee Shop. The F-test indicated that marketing strategy and product quality simultaneously influenced the competitiveness of coffee products at Kiro Lahat Coffee Shop.